2017
DOI: 10.1371/journal.pone.0177229
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes and congenital heart defect prognosis in 53313 non-selected perinatal infants

Abstract: ObjectiveTo evaluate perinatal outcomes and congenital heart defect (CHD) prognosis in a non-selected population.MethodsThe population-based surveillance data used in this assessment of CHDs were based on birth defect surveillance data collected from 2010–2012 in Liuyang City, China. Infants living with CHDs were followed up for 5 years to determine their prognosis. Prevalence, prenatal diagnosis, perinatal outcomes, and total and type-specific prognosis data were assessed using SPSS 18.0.ResultsIn total, 190 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Congenital heart defects (CHD) are the most common birth defect, affecting around 4-8 per 1000 live births and accounting for 30-50% of infant mortalities 1,2 . CHD is believed to result from an interaction between genetic and non-genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart defects (CHD) are the most common birth defect, affecting around 4-8 per 1000 live births and accounting for 30-50% of infant mortalities 1,2 . CHD is believed to result from an interaction between genetic and non-genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart defects (CHD) are the most common forms of birth defects, with an estimated incidence of 4–8 per 1000 live births, and account for 30–50% of cases of infant mortality. It has been hypothesized that the etiology of CHD is multifactorial inheritance resulting from interaction of genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart defects are the most common type of birth defects and have been reported to occur in 4 to 8 of every 1000 live births, [ 14 16 ] accounting for 30% to 50% of birth defects-induced infant mortality. [ 17 , 18 ] Previous studies showed that prenatal detection of CHD may improve pregnancy outcome of fetuses with specific types of cardiac lesions.…”
Section: Discussionmentioning
confidence: 99%